Enhancing the Performance of AlGaN/GaN Schottky Barrier Diodes by SF6 Plasma Treatment and Deep Anode Recess. (1st January 2017) - Wang, Bo-Shiang; Lee, Geng-Yen; Yang, Chun-Chieh; Sanyal, Indraneel; Chyi, Jen-Inn
Abstract : In this work, low turn-on voltage (Von ), low leakage current (IR ) and high breakdown voltage (VBR ) AlGaN/GaN Schottky barrier diodes (SBDs) are fabricated on 6-inch Silicon substrates using an anode recess process combined with SF6 plasma treatment. Using this process, turn-on voltage is reduced from 1.3 V to 0.6 V, compared to the planar untreated devices due to the reduction of Schottky barrier height by having the Schottky metal in contact with the two dimensional electron gas at the AlGaN/GaN interface. Meanwhile, the VBR is increased from 400 V to 455 V due to the presence of plasma implanted fluorine ions near the anode. This process also results in a smaller device capacitance, which leads to the reduction of reverse recovery time from 12.9∼14.4 ns to 9.6∼10.7 ns.